Neuronal nitric oxide synthase is required for erythropoietin stimulated erythropoiesis in mice - Lee, Jeeyoung; Dey, Soumyadeep; Rajvanshi, Praveen K.; Merling, Randall K.; Teng, Ruifeng; Rogers, Heather M.; Noguchi, Constance T. (Frontiers in Cell and Developmental Biology, 2023)
Erythropoietin (EPO), produced in the kidney in a hypoxia responsive manner, is required for red blood cell production. In non-erythroid tissue, EPO increases endothelial cell production of nitric oxide (NO) and endothelial nitric oxide synthase (eNOS) that regulates vascular tone to improve oxygen delivery. This contributes to EPO cardioprotective activity in mouse models. NO treatment in mice shifts hematopoiesis toward the erythroid lineage, increases red blood cell production and total hemoglobin. In erythroid cells, NO can also be generated by hydroxyurea metabolism that may contribute to hydroxyurea induction of fetal hemoglobin. We find that during erythroid differentiation, EPO induces neuronal nitric oxide synthase (nNOS) and that nNOS is required for normal erythropoietic response. Mice with targeted deletion of nNOS (nNOS-/-) have moderately reduced hematocrit. With EPO treatment, nNOS-/- mice show a blunted erythroid response to EPO while hematocrit increase in EPO treated WT and eNOS knockout (eNOS-/-) mice are similar to each other. Erythroid colony assays from bone marrow cells result in comparable numbers from WT, eNOS-/- and nNOS-/- mice at low EPO concentration. Colony number increase at high EPO concentration is seen only in cultures from bone marrow cells of WT and eNOS-/- mice but not from nNOS-/- mice. Colony size with high EPO treatment also exhibits a marked increase in erythroid cultures from WT and eNOS-/- mice but not from nNOS-/- mice. These bone marrow cultures suggest an intrinsic defect in hematopoietic cell response to high EPO stimulation. Bone marrow transplant from nNOS-/- mice into WT mice show engraftment at comparable levels to WT bone marrow transplant. EPO treatment of recipient mice recapitulated the response of donor mice. In mice with nNOS-/- donor marrow, there was a blunted increase in hematocrit after EPO treatment compared with mice that received WT donor marrow. In erythroid cell cultures, addition of nNOS inhibitor resulted in decreased EPO dependent proliferation mediated in part by decreased erythropoietin receptor expression, and decreased proliferation of hemin induced differentiating erythroid cells. These data provide evidence that NO modulates EPO dose dependent erythropoietic response.